2016
DOI: 10.3747/co.23.3114
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Care Plans for People with Colorectal Cancer: Do They Reflect the Research Evidence?

Abstract: AimIn the present study, we synthesized the published literature about the psychosocial aspects of colorectal cancer (crc) survivorship to support an update of the evidentiary base of the survivorship care plans (scps) created in our jurisdiction. MethodsThe psychosocial topics identified in the crc scps created by two different initiatives in our province were used as search criteria: quality of life (qol), sexual function, fatigue, and lifestyle behaviors. An umbrella review was conducted to retrieve the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Information was extracted and synthesized from 51 articles. Table 2 provides a summary of the included studies [15‐65]. Quality analysis, revealed a mean score of 7.7 (±2.0), and median of 8 with a range of 3‐11.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information was extracted and synthesized from 51 articles. Table 2 provides a summary of the included studies [15‐65]. Quality analysis, revealed a mean score of 7.7 (±2.0), and median of 8 with a range of 3‐11.…”
Section: Resultsmentioning
confidence: 99%
“…Some reviews cited that many of the studies examined failed to meet the definition of physical activity [25], whereas others reported well‐defined, if disparate, exercise parameters [15,57,58,63]. The mode of exercise varied widely in reports, spanning both aerobic and resistive training protocols [15,26,27,30,32,35,36,39,45,57,59,60,63,66], as well as described mixed (aerobic plus resistance training) interventions [16,17,19,20,22,24,28,31,32,37,41,43,47,48,53,58,60], yoga [38,47,50,54,64,65,67], tai chi [42,64,65], dance [18], progressive resistive exercise (PRE) [21,30,53], and therapeutic exercises (focused on targeted body region impairments) [21,23,44,53,62]. Exercise programs were structured in various settings (home‐based, outpatient ambulatory clinic, hospital‐based) and provided various levels of provider supervision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline anxiety and depression were low overall in this study, similar to findings in a recent RCT of a nurse-led supportive care intervention in colorectal cancer survivors (Jefford et al, 2016). However, other studies found that CRC survivors experience significant levels of anxiety and distress (D’Souza et al, 2016). Studies show that SCP may lead to improved follow-up care, better long-term physical well-being, positive self-efficacy, improved survivor knowledge on survivorship care, and positive lifestyle changes (Chrischilles et al, 2015; Klemanski et al, 2016; Nissen et al, 2013).…”
Section: Discussionmentioning
confidence: 98%